2006
DOI: 10.1007/s00421-006-0338-y
|View full text |Cite
|
Sign up to set email alerts
|

Influences of tendon stiffness, joint stiffness, and electromyographic activity on jump performances using single joint

Abstract: The present study aimed to examine the influences of tendon stiffness, joint stiffness, and electromyographic activity on jump performances consisting of a single-joint movement. Twenty-four men performed three kinds of unilateral maximal jump using only the ankle joint (squat jump: SJ; countermovement jump: CMJ; drop jump: DJ) on the sledge apparatus. The relative differences in the jump height of CMJ and DJ compared to SJ were defined as pre-stretch augmentation. During jumping exercises, electromyographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
4
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 36 publications
9
93
4
9
Order By: Relevance
“…They suggested that the nervous command of contraction during the isometric training differed from that during the vertical jumping. In addition to this point, some recent observations showed that the mechanical properties of human tendon affected the performances during jumping and/or sprinting exercises (22,24,37). Among them, Kubo et al (22) reported that the tendon stiffness in knee extensors was inversely correlated with the relative difference in jump height between vertical jumps performed with and without countermovement, i.e., prestretch augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the nervous command of contraction during the isometric training differed from that during the vertical jumping. In addition to this point, some recent observations showed that the mechanical properties of human tendon affected the performances during jumping and/or sprinting exercises (22,24,37). Among them, Kubo et al (22) reported that the tendon stiffness in knee extensors was inversely correlated with the relative difference in jump height between vertical jumps performed with and without countermovement, i.e., prestretch augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of plyometric training on patients recovering from knee injuries, especially after articular cartilage repair, are unknown, it may be a critical training method to safely return athletes to full sports participation. 24,60,70,81,87,94,110,120,130,131 Because of the considerable loads and speeds applied to the healing joint with plyometric training, patients should first demonstrate the ability to tolerate the demands of daily activities without pain or swelling. 24 Clinicians must be diligent in monitoring the patient's response to training, using effusion grading and soreness rules.…”
Section: Phase 2: Progressive Joint Loading Andmentioning
confidence: 99%
“…A partir das amostras de sangue foram identificados o pico de concentração de lactato sanguíneo (LACmax) e o percentual de diminuição de lactato sanguíneo (DLS), conforme a equação proposta por Pelayo et al (1996) (DUGAN et al, 2004). Outro fator que pode explicar essa diferença entre as categorias é a eficiência de alguns mecanismos musculoelásticos presentes nas ações musculares realizadas, tais como o stiffness (KUBO et al, 2006) e a rapidez na transição entre as fases excêntrica e concêntrica (KOMI; GOLLHOFER, 1997). De acordo com os autores, essa transição deve ser realizada em um breve espaço de tempo, a fim de evitar a dissipação da energia elástica acumulada nas estruturas musculotendíneas.…”
Section: Protocolo Da Simulação De Lutaunclassified